Cannabidiol and epilepsy in Brazil: a current review - Oshiro, Carlos André; Castro, Luiz Henrique Martins (Arquivos de Neuro-Psiquiatria, 2022)
Background: Cannabidiol (CBD) has become a promising therapeutic option in the treatment of epilepsy. Recent studies provide robust evidence that CBD is effective and safe. Limitations in current knowledge and regulatory issues still limit CBD use. CBD use regarding epilepsy types still lacks clear guidelines. Objective: To critically review the main current pharmacological features and clinical issues regarding CBD use in epilepsy, to provide current regulatory background regarding CBD use in Brazil, and to suggest a practical CBD therapeutic guide in Brazil. Methods: Non-systematic literature review (up to February 2022) of current concepts of CBD and epilepsy, including the authors’ personal experience. Results: Five pivotal trials have led to CBD approval as an adjunctive treatment for Dravet and Lennox-Gastaut syndromes, and for the tuberous sclerosis complex. Efficacy of CBD in other drug-resistant epilepsies remains not completely understood. CBD adverse event profile and drug interactions are better understood. CBD is well tolerated. In Brazil, CBD is not classified as a medication, but as a product subject to a distinct regulatory legislation. CBD is still not offered by the National Brazilian health system, but can be purchased in authorized pharmacies or imported under prescription and signed informed consent. Conclusion:  CBD is a recognized novel treatment for epilepsy. Future well-designed studies and public health strategies are needed to offer widespread access to CBD, and to improve the quality of life of people living with epilepsy in Brazil.
Keywords: Cannabidiol; Epilepsy; Efficacy; Safety; Brazil